2020
DOI: 10.1002/brb3.2007
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, depersonalization, and anxiety contribute to post‐traumatic stress in frontline health workers at COVID‐19 patient care, a follow‐up study

Abstract: Introduction We designed a follow‐up study of frontline health workers at COVID‐19 patient care, within the same working conditions, to assess the influence of their general characteristics and pre‐existing anxiety/depression/dissociative symptoms and resilience on the development of symptoms of post‐traumatic stress disorder (PTSD), while monitoring their quality of sleep, depersonalization/derealization symptoms, acute stress, state anxiety, and burnout. Methods In a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 33 publications
4
84
0
11
Order By: Relevance
“…HCWs include frontline nurses in emergency departments [47] and ICUs [48], Libyan [49] or Indian [50] physicians, Spanish nurses [51], Japanese radiological technologists and pharmacists [52], and others. A state of persistent burnout, that influenced sleep quality, was observed in a longitudinal study on a small group of HCWs [53]. Higher levels of stress [54] and long shifts [55] have been consistently associated with increased levels of BOS in HCWs.…”
Section: Discussionmentioning
confidence: 95%
“…HCWs include frontline nurses in emergency departments [47] and ICUs [48], Libyan [49] or Indian [50] physicians, Spanish nurses [51], Japanese radiological technologists and pharmacists [52], and others. A state of persistent burnout, that influenced sleep quality, was observed in a longitudinal study on a small group of HCWs [53]. Higher levels of stress [54] and long shifts [55] have been consistently associated with increased levels of BOS in HCWs.…”
Section: Discussionmentioning
confidence: 95%
“…While some mitigating interventions including mindfulness, counseling those at risk of burnout, and reducing workload have been proposed as measures to address the widespread burnout of HCWs [9,10,13,15], given the unprecedented surge in the number of COVID-19 cases, individual efforts might not be sufficient to overcome the issue. Recently, psychological resilience has been highlighted as a protective factor against burnout [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Amanullah et al reported that exposure to COVID-19 did not correlate with increased burnout [7]. In contrast, other cross-sectional studies noted that frequent contact with COVID-19 was the most important factor associated with psychological burden and burnout [13][14][15].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The global pandemic has caused considerable stress to many rescuers and nonrescuers alike. Acute stress injury may exacerbate preexisting anxiety, depression, and other psychological illnesses and result in more serious stress disorders (Miguel-Puga et al, 2021 ). Education and increased awareness of stress injuries could be valuable to build resilience and prevent adverse psychological consequences in mountain rescuers (Krystal, 2020 ).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%